If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Ln(1 + -2y) = t (1 * nL + -2y * nL) = t (1nL + -2nyL) = t Solving 1nL + -2nyL = t Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Combine like terms: t + -1t = 0 1nL + -2nyL + -1t = 0 The solution to this equation could not be determined.
| In(3x-2)+in(x-1)=2inx | | -2(2x-3)=32 | | 3u-14=40 | | -32=-35-5n^2 | | 6=2v-16 | | 5x-2=7(2x-8) | | 2y-15=19 | | 7n^2-11n=-4 | | 9+16-9(1)2= | | r^2-4r-15=-3 | | x/9=1/6 | | 3lnx-lny=0 | | (Y-18)/6=0.7 | | -3(-5-b)=.33(b+13) | | (Y-18)/6 | | 12+8k=84 | | Y-18/6 | | 0.6(t+36)=-3(4-t) | | 19x+(-9)=-29+14x | | 12b+12b=3 | | 5/8x40 | | 9-w=215 | | 1/3.(180-×) | | 3y-15=33 | | (7-7x^2)/7 | | 12x+42=10x+50 | | 17x-1=135 | | X^2-20-3x-20=0 | | 12x-6+6=36 | | 1/-76=1/x | | -2x+8=4(x+8) | | 7=(-3)+x |